E-Learning amid COVID-19 Pandemic: An Experience by medical students of Rawalpindi Medical University Pakistan - Rizwana Shahid, Shazia Zeb, Sumaira Yasmeen, Muhammad Umar, Rai Muhammad Asghar, Yumna Hafeez, Rizwana Shahid, Shazia Zeb, Sumaira Yasmeen, Muhammad Umar, Rai Muhammad Asghar, Yumna Hafeez (Journal of Rawalpindi Medical College, 2020)
Objectives: To determine the effectiveness of e-learning and hurdles confronted to the undergraduate medical students of Rawalpindi Medical University in continuation of academics during COVID-19 pandemic. Subjects & Methods: A survey was carried out during July 2020 to scrutinize the experience of 1041 medical students enrolled at Rawalpindi Medical University regarding their academic experience through Microsoft Teams. A self- structured questionnaire was digitally administered for this purpose to gather their responses about academic coverage, prior intimation about the lecture topic, opportunities for interaction with teachers, internet connectivity and various teaching methods employed by the teachers and recommendations for improvement. The data was analyzed by means of SPSS version 25.0. Percentages were computed for responses on all the variables. Results: Total 1041 medical students gave feedback regarding their e-learning through Microsoft Teams. Theoretical aspect coverage, prior intimation of topic to be covered and student-teacher interaction during online classes were satisfactory according to 68%, 85% and 61% of students respectively. About 70% respondents claimed frequent internet connectivity issues during e-learning while 63% found Microsoft Teams interface incompatible. Broad band internet connection at home was available to only 60.10% students. Most (25%) students wanted improvement in software for smooth execution of their e-learning. Conclusion: Although online learning proved as blessing in disguise amid COVID-19 pandemic but being new experience for both students and teachers some problems were faced that can easily be rectified.